Potential Target Antigens for a Universal Vaccine in Epithelial Ovarian Cancer. (1st August 2010) - Vermeij, Renee; Daemen, Toos; de Bock, Geertruida H.; de Graeff, Pauline; Leffers, Ninke; Lambeck, Annechien; ten Hoor, Klaske A.; Hollema, Harry; van der Zee, Ate G. J.; Nijman, Hans W.
Abstract : The prognosis of epithelial ovarian cancer (EOC), the primary cause of death from gynaecological malignancies, has only modestly improved over the last decades. Immunotherapeutic treatment using a cocktail of antigens has been proposed as a "universal" vaccine strategy. We determined the expression of tumor antigens in the context of MHC class I expression in 270 primary tumor samples using tissue microarray. Expression of tumor antigens p53, SP17, survivin, WT1, and NY-ESO-1 was observed in 120 (48.0%), 173 (68.9%), 208 (90.0%), 129 (56.3%), and 27 (11.0%) of 270 tumor specimens, respectively. In 93.2% of EOC, at least one of the investigated tumor antigens was (over)expressed. Expression of MHC class I was observed in 78.1% of EOC. In 3 out 4 primary tumors, (over)expression of a tumor antigen combined with MHC class I was observed. These results indicate that a multiepitope vaccine, comprising these antigens, could serve as a universal therapeutic vaccine for the vast majority of ovarian cancer patients.